Empreendedorismo público na gestão municipal: o caso do plano de desenvolvimento de competências da prefeitura de Curitiba - Pessin, Maria Aparecida (2013)
This paper discusses the importance of entrepreneurship in the Brazilian public sector by analyzing the entrepreneurial initiatives in managing people through competence development and strategies to improve management and administration performance of municipal administration. In the search to improve its performance, the public administration undergoes several improvement processes that change social, economic, environmental and cultural spheres, affecting communication dynamics and access to products and services, establishing paradigms on life quality and well-being to society and consequently improving processes and public functions standards. Regarding this subject, the discussion about the entrepreneurship associated to the public service action is still incipient in the academy and the government. Although, this becomes an important subject to understand changes and act in the constantly changing scenario. Thus, considering the modernization and professionalization necessities of the public administration and the public server managers to cope with the emergent demands from the population, it is possible to highlight the following question as the main interrogation in this research: Can the skill managing plan from the Curitiba Municipal Administration be considered as an entrepreneurship action? Additionally, to complement this study, the following objectives are defined: Present the main changes occurred to Brazilian public management from the discussion about the state improvement and the current managing models since the First Brazilian Republic historical period; Discuss the public entrepreneurship and skills management concepts; Distinguish the Curitiba Municipal Administration profile regarding its organizational characteristics, skills managing model and public entrepreneurship. Regarding the methodology, it is a study case from the Curitiba Municipal Administration (PMC) from the Municipal Institute of Public Administration (IMAP), from 2009 to 2012, the period when management contracts and cooperation agreements were adopted as instruments to alignments in the municipal administration. It is also the moment in which the skills development management plan is considered an instrument to manage changes. The approach to the problem is qualitative and considers the investigation of evidences to validate correct understanding. The methods used were observational analysis of the facts in the current period, document research and survey the PMC managers (directors, coordinators, techs, secretaries and presidents). The results demonstrated advances in discussion to improve the understanding of questions about entrepreneurship in public administration with objective to offer arguments to the efficacy of public policies. The conclusion is that, despite the lack of acceptance and understanding of the public entrepreneurship, the daily actions demonstrated evolution of the public administration showing the possibility to adopt the public entrepreneurship as a resource to improve the public administration.